Teaching English to Young Children - Gautam, Ganga Ram (Journal of NELTA Surkhet, 2015)
In the context of Nepal, teachers often prefer to teach at the higher level. In my professional career, I have met very few people who really enjoy teaching at the preprimary or primary level. According to them, teaching young children is very challenging and managing learning at that level is very difficult. My experience is different. I have taught the young children for some time in the past and I enjoyed it very much. Children bring a lot of energy and enthusiasm and if a teacher can make use of that energy in creating learning atmosphere in class, both the children and teacher enjoy being in the pre-primary and primary classes. This article presents some observations and activities to encourage teachers to teach English at the pre/primary level and make English teaching a fun experience. Journal of NELTA Surkhet Vol.4 2014: 26-33